The Validity of Question Wheel "KARUNIA" Learning Media in the Archaebacteria and Eubacteria Students of Class X IPA of SMAN 7 Banjarmasin - Karunia Soliha Septiani; Noorhidayati Noorhidayati; Maulana Khalid Riefani (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
Effective learning is when students are actively involved in the learning process, so they can gain an understanding of the learning process carried out and can improve learning outcomes on the concept of learning. Archaebacteria and Eubacteria are biological concepts that are relatively difficult, abstract, and tend to memorize. Therefore research and development of fun learning media are carried out in the form of a Question Wheel game "KARUNIA". This research and development are to describe the validity of the "KARUNIA" Question Wheel learning media. This type of research is research and development with 4D models. This research is limited to the Develop stage. The results of research and development carried out on the "KARUNIA" Question Wheel learning media on the Archaebacteria and Eubacteria concepts are classified as very valid with a value of 88%.AbstrakPembelajaran yang efektif adalah apabila siswa ikut terlibat aktif dalam proses pembelajaran, sehingga dapat memperoleh pemahaman dari proses pembelajaran yang dilakukan dan dapat meningkatkan hasil belajar pada konsep pembelajaran. Archaebacteria dan Eubacteria merupakan konsep Biologi yang relatif sulit, abstrak, dan cenderung menghafal. Maka dari itu dilakukan penelitian dan pengembangan media pembelajaran yang menyenangkan berupa permainan Question Wheel “KARUNIA”. Tipe penelitian R&D ini untuk mendeskripsikan validitas media pembelajaran Question Wheel “KARUNIA”. Jenis penelitian ini merupakan penelitian dan pengembangan dengan model 4D. Penelitian ini dibatasi sampai tahap Develop (pengembangan). Hasil penelitian dan pengembangan yang dilakukan pada media pembelajaran Question Wheel “KARUNIA” pada Konsep Archaebacteria dan Eubacteria tergolong sangat valid dengan nilai 88%.